The Phenomenon of War Flaming on Writing in Social Media: The Effect of Echo Chamber and Filter Bubble Algorithm in Digital Citizenship - Melisa Arisanty; Yasir Riady; Sri Maulidia Permatasari; Selly Anastassia Amellia Kharis; Kamrin Mir; Muhammad Ajmal (Jurnal Kewarganegaraan, 2026)
Echo Chamber and Filter Bubble are two subjects now under extensive discussion. The growing prevalence of social media in recent years underscores the potential effects of the Echo Chamber and Filter Bubble phenomena. One of them is the conflict raging on social media. The attributes of the Echo Chamber and Filter Bubble can influence the prevalence of war flame on social media. This study aimed to examine the impact of the Echo Chamber and Filter Bubble on War Flaming. This study used a quantitative methodology to investigate the relationship among the three ideas. The sample was chosen through selective sampling, comprising 100 respondents identified as flame perpetrators. The study's results indicate a significant correlation between Echo Chamber and Filter Bubble phenomena and the prevalence of war flame on social media. This study demonstrates that Echo Chamber and Filter Bubble significantly influence War Flaming. Echo Chamber (X1) and Filter Bubble (X2) collectively account for 41.8% of the variance in War Flaming (Y). The results indicate that preventing war escalation is challenging due to the existence of echo chambers and filter bubbles, unless stringent content restriction policies are implemented by social media companies and enhanced self-awareness is cultivated from an early age through familial, social, and educational influences.